Teredo navalis in the Baltic Sea: Larval Dynamics of an Invasive Wood-Boring Bivalve at the Edge of Its Distribution - Lippert, Heike; Weigelt, Ronny; Glaser, Karin; Krauss, Rica; Bastrop, Ralf; Karsten, Ulf (Frontiers in Marine Science, 2017)
Wooden groin systems on the southwestern Baltic Sea coast are a traditional and important coastal-protection facility, but have been regularly infested and destroyed by the wood-boring bivalve Teredo navalis since the early 1990s. The occurrence of T. navalis was presumed to be limited mainly by the prevailing low salinities. Recently, a possible range expansion of this invasive species to the more eastern parts of the Baltic Sea has been discussed. T. navalis larval settlement was therefore monitored at the distribution boundary of the species in the Baltic Sea over a period of four years. At seven stations along the prevailing salinity gradient on the Mecklenburg-western Pomeranian coast, larval traps were installed at regular time intervals, while at the same time water temperature and salinity were measured continuously every hour. Correlations between measured abiotic parameters and borehole abundance of T. navalis were tested. For the German Baltic Sea coast, no range expansion of T. navalis was confirmed. The salinity and temperatures at the groin systems varied among the study years, and significant correlations between T. navalis borehole abundance and salinity as well as temperature were found. Higher summer temperatures favor the T. navalis borehole abundance on the Mecklenburg-western Pomeranian coast, and may slightly shift the distribution border of this species toward lower salinities.